Characterization of lipid productivity and fatty acid profile of three fast-growing microalgae isolated from Bengkulu for possible use in health application - Praharyawan, Swastika; Rahman, Delicia Yunita; Susilaningsih, Dwi (Journal of Tropical Life Science, 2016)
Three strains of fast-growing microalgae were investigated in this study for their potential of lipid production and its possible use in health application. Lipid content, lipid productivity, and fatty acids profile of the 3 mi-croalgae strains were also analyzed. The strain of LBB13-2-AL045 and LBB13-2-AL048 possessed highest lipid content (49.08 Â± 0.25%) and lipid productivity (40.27 Â± 1.91 mg.L-1.day-1), respectively, among the other tested strains. The fatty acids profile from the 3 strains exhibited its possible use in health application. The two strains of LBB13-2-AL046 and LBB13-2-AL048 possessed high valuable fatty acids of polyunsaturated fatty ac-ids (PUFA) omega-3 and omega-6, whereas LBB13-2- AL045 possessed balance ratio of saturated fatty acid (SFA) : monounsaturated fatty acid (MUFA) : PUFA (1 : 1.3 : 1) as is recommended by American Heart As-sociation (AHA) (1 : 1.4 : 0.8). The high content of omega-3 and omega-6 fatty acids indicated that the algal lipids of two strains (LBB13-2-AL046 and LBB13-2-AL048) were potential to be applied in cardiovascular health. The balance ratio of SFA : MUFA: PUFA as is recommended by AHA indicated that the algal oil of LBB13-2-AL045 strain was recommended in order to generate the best LDL/HDL ratio.